Produção do espaço sagrado na arquitetura contemporânea: a interpretação da tradição católica a partir do século XX - Daniela Duarte de Freitas Oliveira (2010)
This study focuses on the Catholic religious architecture from the twentieth century aiming to seize the symbolic permanencies reachable by modernist and contemporary architects to give shape and representation to the temple, during a period said desecrated due to its plural materialism and spiritualism. Fundamentally, provides an overview of a historiographical panorama which serves as a foundation for the analysis of contemporary production, compiling and systematizing part of ecclesiastic legacy designed and/or built from the mid- 19th and 20h centuries. In synchrony, presents its conditions of origin, reasons and meanings, and considers how the assumption of modernism and the reform movements like the Liturgical Movement and the II Vatican Council were applied to architectural fact of new churches in order identify the strategies and modern signs valid in contemporary architectural practice.